The Role of Indonesian Politics Diplomacy Towards Saudi Arabia In Enhancement of Hajj Pilgrimage Quota After Covid-19 Pandemic - Panggih Prabowo Rona Saputra (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2023)
Mostly Muslim knew that one of the fifth pillars of Islam is Hajj. Hajj for those who are physically and financially able, Muslims around the world perform the pilgrimage once a year. During Dzulhijah otherwise known as the month of Hajj, pilgrims visit a number of locations in Saudi Arabia. The research method this time uses a qualitative method with a literature review. Data collection is done through books, journals, results, previous research and other sources. Indonesia is a nation that consistently seeks to advance its international interests through diplomacy with destination countries. Indonesia has a powerful impact with a large Muslim population. Considering that the allocation for the pilgrimage to Mecca is determined by the 1:1000 rule, the amount of political lobbying required to fulfill the request for additional allocations for the pilgrimage from the Government of the Republic of Indonesia to the Government of Saudi Arabia is very large. Hajj and Umrah Indonesia should be able to further develop its capacity in formulating government policies in the future regarding the implementation of Hajj and Umrah after the COVID-19 outbreak.